Technical and Economic Assessment for using Ground-Source Heat Pumps in Commercial and Institutional Buildings - Hossein Shahinzadeh; Hajar Ghotb (International Journal of Electrical and Computer Engineering (IJECE), 2012)
One of the most important methods proposed for reduction of consumed energy in facility and ventilation systems in a building is application of ground source heat pumps (GSHPs). With regard to the enhanced use of such pumps in providing heat and cold demands in homes, commercial centers, institutions and industrial buildings analysis of their performance as well as their benefits and deficiencies compared to common ventilation systems have gained interest of many researchers. Such systems apply ground as a thermal well in summer and as a heat source in winter. They can be used in various climatic conditions in different regions. They have no combustion and they only transfer heat. In the present article first, performance conditions of ground source heat pumps (in two modes of heating and cooling) are analyzed. Then in order to assess the performance of proposed model economically, its application in Iran will be studied. Finally after introducing the proposed plan and by concluding the overall results the return time for investment will be estimated. The obtained results from graph analysis would indicate the superiority of proposed model over other plans and also it provides an appropriate general context for the researchers for a better understanding and examining this system in comparison to other systems.DOI:http://dx.doi.org/10.11591/ijece.v2i4.1463